2016
DOI: 10.1038/bjc.2016.188
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian randomisation analysis strongly implicates adiposity with risk of developing colorectal cancer

Abstract: Background:Observational studies have associated adiposity with an increased risk of colorectal cancer (CRC). However, such studies do not establish a causal relationship. To minimise bias from confounding we performed a Mendelian randomisation (MR) analysis to examine the relationship between adiposity and CRC.Methods:We used SNPs associated with adult body mass index (BMI), waist-hip ratio (WHR), childhood obesity and birth weight as instrumental variables in a MR analysis of 9254 CRC cases and 18 386 contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 26 publications
5
58
2
Order By: Relevance
“…It is noteworthy that none of the IV SNPs for TC also represent IVs for obesity, supporting an independent relationship between TC and CRC. As illustrated here and in previously studies of obesity and CRC, insulin levels and uterine cancer, and lipid levels and coronary heart disease, MR provides an attractive means of establishing causal associations. In addition to demonstrating an association between TC and CRC risk we found that genetic variants that mimic the effect of HMGCR inhibition were associated with a reduced CRC risk, supporting findings from observational epidemiological studies that statins have beneficial effect on the population burden of CRC.…”
Section: Discussionmentioning
confidence: 71%
“…It is noteworthy that none of the IV SNPs for TC also represent IVs for obesity, supporting an independent relationship between TC and CRC. As illustrated here and in previously studies of obesity and CRC, insulin levels and uterine cancer, and lipid levels and coronary heart disease, MR provides an attractive means of establishing causal associations. In addition to demonstrating an association between TC and CRC risk we found that genetic variants that mimic the effect of HMGCR inhibition were associated with a reduced CRC risk, supporting findings from observational epidemiological studies that statins have beneficial effect on the population burden of CRC.…”
Section: Discussionmentioning
confidence: 71%
“…Although peripherally located adiposity is relatively inert from a metabolic standpoint, centrally located adiposity releases proinflammatory chemokines, such as tumor necrosis factor-a and interleukin-6, which have a range of deleterious effects from insulin resistance to cancer risk. [77][78][79] In regards to mucosal permeability, there are data showing that these proinflammatory chemokines alter the tight junction protein composition. 80 A good example of this is with the tight junction composition in active EoE.…”
Section: Eosinophilic Esophagitismentioning
confidence: 99%
“…Despite the potential of subtype‐specific analyses to yield important information on the link between body fatness (an established CRC risk factor), metabolic health, and CRC development, data are limited. Body fatness or poor metabolic health may either cause specific molecular errors in specific developmental pathways of CRC, or contribute to a colorectal microenvironment favorable for tumors with specific molecular features to grow, for instance, through chronic low‐grade inflammation .…”
Section: Introductionmentioning
confidence: 99%